Estimating the Cost of Cancer Care in British Columbia and Ontario: A Canadian Inter-Provincial Comparison - De Oliveira, Claire (Healthc Policy, 2017)
BACKGROUND: Costing studies are useful to measure the economic burden of cancer. Comparing costs between healthcare systems can inform evaluation, development or modification of cancer care policies. OBJECTIVES: To estimate and compare cancer costs in British Columbia and Ontario from the payers' perspectives. METHODS: Using linked cancer registry and administrative data, and standardized costing methodology and analyses, we estimated costs for 21 cancer sites by phase of care to determine potential differences between provinces. RESULTS: Overall, costs were higher in Ontario. Costs were highest in the initial post-diagnosis and pre-death phases and lowest in the pre-diagnosis and continuing phases, and generally higher for brain cancer and multiple myeloma, and lower for melanoma. Hospitalization was the major cost category. Costs for physician services and diagnostic tests differed the most between provinces. CONCLUSIONS: The standardization of data and costing methodology is challenging, but it enables interprovincial and international comparative costing analyses.